Specific Nature of Professional Preparation of a Teacher of Choreography in Pedagogical Higher Educational Establishment - Olena Yefimchuk (Pedagogical Discourse, 2012)
The specific nature of professional preparation of a teacher of choreography in pedagogical higher educational establishment is studied in the article. The article deals with the bases of professional forming of the future choreographers by means of special disciplines as well as necessary condition under which professional preparation of a teacher of choreography is done.